A 30GHz bandwidth driver amplifier with high output voltage swing for ultra-wideband localization- and sensor systems - Sewiolo, Benjamin; Rascher, Jochen; Weigel, Robert (Asia-Pacific Microwave Conference, 2008, 2008)
This paper reports on the analysis, design and characterization of a 30 GHz lumped broadband driving amplifier for ultra-wideband localization and sensor systems. The circuit integrates a cascode differential stage, which is fed by two cascaded emitter-followers (EF). The differential gain is 10 dB with a gain flatness of plusmn1 dB in the desired frequency range. This amplifier exhibits an output 1-dB compression point of 12 dBm. The maximum differential output voltage swing is 3.2 Vpp. The amplifier consumes a power of 560 mW at a supply voltage of plusmn3.3 V. The compact 0.5 mm2 amplifier is manufactured in a low-cost 0.25 mum SiGe BiCMOS technology with a transit frequency of 75 GHz.
elib2cris::1512001600,sewiolo2008c